Hallucinations as a trauma-based memory: implications for psychological interventions - Steel, Craig (Frontiers in Psychology, 2015)
The relationship between hallucinations and life events is a topic of significant clinical importance. This review discusses the extent to which auditory and visual hallucinations may be directly related to traumatic events. Evidence suggests that intrusive images occur frequently within individuals who also report hallucinatory experiences. However, there has been limited research specifically investigating the extent to which hallucinations are the re-experiencing of a traumatic event. Our current theoretical understanding of these relationships, along with methodological difficulties associated with research in this area, are considered. Recent clinical studies, which adopt interventions aimed at the symptoms of posttraumatic stress disorder in people diagnosed with a psychotic disorder, are reviewed. There is a need for the development of evidence-based interventions in this area.